CONCEPTUAL APPROACHES AND METHODS FOR DETERMINING THE INVESTMENT ATTRACTIVENESS OF THE NATIONAL ECONOMY (Economic journal of Lesya Ukrainka Volyn National University, 2018)
Investment attractiveness is a collection of objective and subjective conditions that contribute or hinder the process of investment in the economy of the country at the micro, meso and macro levels. There are different approaches and methods for assessing investment attractiveness, but they can be divided into three main groups:1. Statistical approach. It is based on the analysis of statistical data concerning the inflow of investments into the national economy. This approach is based on the assumption that high statistical indicators are the basis for the high investment attractiveness of the economy.2. Expert evaluation method. When using this method, the expert provides his own assessment of the significance of the indicators, ie chooses the most important indicators, after which the analysis of these indicators in the dynamics is conducted and conclusions are drawn regarding the investment attractiveness of the region.3. Rating approach. In assessing the investment attractiveness of the national economy, two varieties of this approach can be distinguished: a rating-analytical and rating approach based on surveys.To evaluate the investment attractiveness of the economy can be used indicators characterizing investment activity. Analysis of these indicators allowed to divide them into three groups: general, macroeconomic indicators and indicators of investment market valuation.The traditional assessment of investment attractiveness is related to the calculation of the integral indicator and the corresponding rating of the countries by establishing their investment rating based on an analysis of the factors of the political, economic, socio-cultural, institutional environment, resources and infrastructure.The main factors on the basis of which one can assess the investment attractiveness of the country’s economy: socio-political stability; level of capacity and solvency of the domestic market; the level of stability and operation of the credit and financial banking system; the level of inflation in the country; the level of corruption in economic spheres; degree of legal support of investment activity; the level of stability of the regulatory framework for entrepreneurial and investment activity; stock market development; tax policy; level of technology development; level of development of innovation activity.
Keywords: investment attractiveness, investment attractiveness assessment, national economy, macro level, direct foreign investment, investment security, economic growth